The Implementation of Moral and Character Values Education in the Islamic Competition in Kutoharjo Village - M. Adib Musthofa; Najwa Abriellia; Nurul Latifatul Azkiyani; Salsabila Salsabila; Shalahuddin Al-Ayyubi; Zuanita Adriyani (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education of moral values and character is very important in shaping the personality of children with noble character. The implementation of this education can be done through various activities, one of which is Islamic competitions. The purpose of this study is to explore how the implementation of Islamic competitions can be an effective means of internalizing moral and character values, as well as its impact on the social life of the Kutoharjo Village community as a whole. Researchers used qualitative methods, with data collection techniques of observation, interviews, and documentation. Then continued to analyze the data by using data reduction techniques, presenting data, and drawing conclusions. The Islamic competition in Kutoharjo Village, as part of the KKN UIN Walisongo program, plays an important role in shaping the character of the younger generation through the cultivation of moral and religious values. By involving 29 children aged 5-12 years in adhan, tartil, and short surah memorization competitions, this activity provides an opportunity for children to develop their talents, increase self-confidence, and spread the values of patience, honesty, tolerance, and peace in the community.